DIGITAL TRANSFORMATION IN THE INSURANCE INDUSTRY - Шевчук, Олександра (Socio-economic relations in the digital society, 2019)
The change of generations and technological progress inevitably bring and actualize the digital transformation in all spheres of activity, including the insurance industry, and insurers must be ready for this. First of all, innovations are critically needed to meet the needs of clients in a more efficient way, to involve and keep them with convenient new quality services. At the same time, by means of innovations, insurers can reduce costs and increase the efficiency of business processes. Long-term prospects for the growth of the insurance industry lie in innovative insurance products and services. The purpose of the article is to reveal the possibilities of digital technologies in improving the effectiveness of the insurance business model, as well as to identify key changes in the insurance industry, in accordance with the requirements of time and a new generation of customers. The result of the analysis is the conclusion that those companies that will not feel the need for innovation on time will have signifi cantly higher cost ratios in the future (as compared to innovative competitors), as well as anti-selection of risks, because innovations provide access to lower risk customers, for whom it becomesprofitable to use individualized products. The article also substantiates the fact that insurers will play a greater role in preventing risks in the future than in compensation for losses. This hits the volume of demand for insurance services, but risk mitigation becomes a new value proposal in the insurance model. Today, insurers need to analyze the innovation landscape, compare their internal technological capabilities with solutions developed by Insurtech companies and consider their options for moving forward — from digitizing transactions to to acquiring or partnering with Insurtechs.
Keywords: digital technology; innovation; insurance; Insurtech; insurance business model